Transformation of State Islamic Higher Education Institutions in Small District Cities - Mashudi Mashudi; Risdiana Himmati; Wahyu Dwi Warsitasari (Al-Hayat: Journal of Islamic Education, 2022)
The purpose of this study is to analyze the economic value of land conversion into educational investment land, as well as a driver of increasing the income of the surrounding community because the main factor is the Higher Education Institution of the State Islamic University (UIN) Tulungagung which also includes an educational investment program for the long-term state. Because the growth of education also affects economic growth and vice versa. This study uses an interpretive paradigm through a qualitative approach; the type of case study uses logistic regression analysis. The source of research data is the land owner's reason for selling his land to be used as an educational institution. The results of the study [1] four factors affect the opportunity for land conversion, namely (a) the educational background of the land owner will be aware of, and the importance of Islamic education, (b) the area of land owned, (c) financial income and (d) the location that refers to on the distance to UIN Tulungagung; [2] Investment in land transfer for education because Indonesia's demographics are dominated by young people whose thinking paradigm is far ahead for the future of Islamic education for the nation's children, the focus of the Indonesian government is to invest in human resources in preparing superior Islamic Human Resources through education; [3] The use of logistic regression analysis limits generalizability, as the sample design cannot be considered to characterize all landowners in turning it into an educational investment.